2021
DOI: 10.1108/ijebr-12-2019-0699
|View full text |Cite
|
Sign up to set email alerts
|

Pivot decisions in startups: a systematic literature review

Abstract: PurposeEntrepreneurs' pivot decisions are poorly understood. The purpose of this paper is to review the existing literature on pivot decisions to identify the different conceptualizations, research streams and main theoretical building blocks and to offer a baseline framework for future studies on this phenomenon.Design/methodology/approachA systematic literature review of 86 peer-reviewed papers published between January 2008 and October 2020, focusing on the pivot decision in startups, was performed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 133 publications
0
33
0
Order By: Relevance
“…The Albanian entrepreneurs appear to be determined to implement their original business idea in comparison to their Greek peers, whose answers indicated that they are more likely to pivot their idea and implement a different idea than the original one, or even implement more than one business idea. This particular finding may indicate that because of the particular entrepreneurial ecosystem conditions in Albania, which renders it in a still nascent position, the ability to recognize alternative business opportunities and ways to seize them is relatively low [58].…”
Section: Discussionmentioning
confidence: 97%
“…The Albanian entrepreneurs appear to be determined to implement their original business idea in comparison to their Greek peers, whose answers indicated that they are more likely to pivot their idea and implement a different idea than the original one, or even implement more than one business idea. This particular finding may indicate that because of the particular entrepreneurial ecosystem conditions in Albania, which renders it in a still nascent position, the ability to recognize alternative business opportunities and ways to seize them is relatively low [58].…”
Section: Discussionmentioning
confidence: 97%
“…The decision to pivot involves uncertainty as it may jeopardise the firm's survivability. Due to this uncertainty, it is challenging to determine what, when and how to pursue a pivot (Flechas Chaparro and de Vasconcelos Gomes, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, they pointed out that the concept of entrepreneurial pivoting has not gained much attention among researchers. Whereas Flechas Chaparro and de Vasconcelos Gomes (2021) conducted a systematic literature review on pivoting decision in startups. This study provided a comprehensive review on the pivot decision in startups, including discussion of prior definitions as well as proposing a refined definition of entrepreneurial decision making.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the assessment of an alternative’s viability requires in itself some degree of resource commitment—previous studies have referred to this trade-off as the paradox of entrepreneurship ( Gans et al, 2019 ). In this sense, recent literature has reported that entrepreneurs cope with the uncertainty of the unfolding context they operate in by pivoting ( Berends et al, 2021 ; Flechas Chaparro and de Vasconcelos Gomes, 2021 ). A pivot represents a strategic reorientation that enables firms to probe new hypotheses about their business model ( Frederiksen and Brem, 2017 ), rapidly collecting information about its potential viability ( Contigiani and Levinthal, 2019 ; Eisenmann et al, 2013 ; McDonald and Eisenhardt, 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%